2022
DOI: 10.3389/fpsyg.2022.992665
|View full text |Cite
|
Sign up to set email alerts
|

Teaching style and academic engagement in pre-service teachers during the COVID-19 lockdown: Mediation of motivational climate

Abstract: COVID-19 and the resulting confinement has had a great impact on the educational environment. Although research in initial teacher education has focused on studying the factors that lead to increased academic engagement, there is no evidence that examines the role of teacher interpersonal style and motivational classroom in a virtual learning context. The aim of this research was to analyze the mediating role of motivational climate between teacher interpersonal style (i.e., autonomy support and controlling st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Recent advances in the educational field have tried to examine how socio-contextual classroom environments (i.e., the social-psychological environment) affect motivational processes, as well as the role the teacher trainer might adopt in the initial teacher training context [11][12][13][14]. In this sense, following self-determination theory (SDT) [15], various interpersonal teaching styles are recognised (e.g., autonomy support and controlling style) in the teaching intervention.…”
Section: Of 14mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in the educational field have tried to examine how socio-contextual classroom environments (i.e., the social-psychological environment) affect motivational processes, as well as the role the teacher trainer might adopt in the initial teacher training context [11][12][13][14]. In this sense, following self-determination theory (SDT) [15], various interpersonal teaching styles are recognised (e.g., autonomy support and controlling style) in the teaching intervention.…”
Section: Of 14mentioning
confidence: 99%
“…Previous research [33] has operationalized academic engagement across different dimensions: vigour, dedication, and absorption. Specifically, research in the teacher training context has shown the importance of academic engagement both as a consequence of socio-contextual classroom environments [14] and as a mediator between educational outcomes [13]. Although the use of academic engagement as an antecedent of future behaviours has been evidenced [34], few studies have evaluated its possible positive influence on behavioural intention (i.e., the intention to be a teacher) [35] despite its relevance in the teacher training context [8,10,36].…”
Section: Academic Engagementmentioning
confidence: 99%
“…Some studies [8,9] show that the teacher's role can be seen as one of the reasons for generating discipline in the PE classroom; so much so that some authors highlight the motivational climate generated by the teacher in the classroom as being responsible for the students' successful or failing behaviors [10]. Previous surveys [8,11] have demonstrated the need to investigate in more detail the role played by the teacher in sustaining discipline and influencing the social environment in the classroom. However, to date, we are unaware of any research that has examined the effects of the PE-teacher-generated social climate in the classroom on subject satisfaction.…”
Section: Introductionmentioning
confidence: 99%